Characterization of hams added with nut residual pastes from the mechanical extraction of oil - Luna, Juan (2013)
Nuts contain in their composition nutrients and bioactive compounds that when consumed in sufficient amounts may provide health benefits. In this study was evaluated the influence of the addition of residual pastes (10%), obtained from the extraction of oil from walnut (Juglans regia L.), pecan (Carya illinoinensis (Wangenh.) K. Koch), variety Western Shley, and peanut (Arachis hypogaea), on the modification of some textural, proximate, physicochemical, microbiological and sensory characteristics of cooked hams. Hams were stored at 4 ° C for 21 days. Hams containing pastes significantly increased (P ≤ 0.05) the protein, fat, and total fiber content. Hams added with paste presented a less rigid structures (P ≤ 0.05). The color parameters (L*, a*, and b*) of hams decrease slightly during the storage time, except for the ham added with walnut paste, which was darker. The nut pastes contributed significantly (P ≤ 0.05) to decrease the shelf life of hams. However, the yeast and mold counts in ham were less than 10 CFU/g at 21 days of storage. aw and pH decreased significantly (P ≤ 0.05) and syneresis increased during storage. Hams added with residual pastes were well sensory accepted regarding color, aroma, taste, appearance, and overall acceptability.